Analysis of a sea urchin gene cluster coding for the small nuclear U7 RNA, a rare RNA species implicated in the 3' editing of histone precursor mRNAs. - De Lorenzi, M (1986)
A genomic 9.3-kilobase DNA fragment of the sea urchin Psammechinus miliaris, containing a cluster of five U7-RNA genes (or pseudogenes), has been isolated and analyzed by partial DNA sequencing. The U7-RNA coding sequences differ from one another by one or two nucleotides, one of the five gene sequences being identical to those of the cDNA U73 clone prepared earlier [Strub, K., Galli, G., Busslinger, M. & Birnstiel, M. L. (1984) EMBO J. 3, 2801-2807]. The spacer sequences separating the genes have, on the whole, a low degree of homology; hence, the five genes must have arisen by an ancient duplication event. The sequences preceding the coding portion contain three highly conserved sequence motifs but no "TATA box." The 3' flanking sequences include a highly conserved AAAGNNAGA sequence that is held in common with other U-RNA genes from both sea urchins and vertebrates. Our findings confirm our classification of the U7 RNA as a genuine, if sparsely represented, member of the U-RNA family.